In vivo and in vitro studies using larval and adult antigens from Neobenedenia melleni on immune response in yellowtail (Seriola lalandi). Issue 11 (19th April 2017) - Reyes‐Becerril, M; Alamillo, E; Trasviña, A; Hirono, I; Kondo, H; Jirapongpairoj, W; Ascencio‐Valle, F; Angulo, C
Abstract: Neobenedenia melleni is a monogenean parasite that causes significant mortality and economic losses in fish aquaculture. Changes in the antigenic composition of this parasite occur during its developmental stages. In this study, we evaluated humoral parameters in serum and transcriptional immune responses of yellowtail naturally infected with N. melleni . In addition, in vitro assays were performed to study the stimulatory effects of antigens from larvae and adults on spleen leucocytes from non‐infected fish at 6 and 24 h post‐stimulation. The results showed enhanced total protein, myeloperoxidase and antiprotease activities in N. melleni ‐infected fish compared with non‐infected ones. The induction of Toll‐like receptors (TLRs) and pro‐inflammatory cytokines in spleen leucocytes during natural infection with N. melleni suggests that these immune‐related genes play an important role in the initiation of the immune defence mechanism for controlling parasite infection. Interestingly, the magnitude of in vitro responses of spleen leucocytes was dependent on the parasitic stage. An important stimulation of gene expression by adult antigens on spleen leucocytes was observed. Differential expression patterns of TLRs and target cytokines in yellowtail leucocytes in both in vivo and in vitro studies suggest that the quality of yellowtail immune response is conditioned by N. melleni development.